MRI of cardiovascular malformations - Kastler, Bruno; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
MRI is a non-invasive and non-ionizing imaging modality that is perfectly suited for the diagnosis and follow-up of both pediatric and adult congenital heart disease. It provides a large field of view and has the unique ability to depict complex cardiac and vascular anatomy and to measure cardiac function and flow within one examination. MRI is the ideal complement to echocardiography whenever the information provided by the latter is limited. This book has been conceived as a self-teaching manual that will assist qualified radiologists, cardiologists, and pediatricians, as well as those in training. It is richly illustrated with numerous images and drawings that cover all usual and most unusual anomalies. The principal author, Professor Bruno Kastler, is head of radiology at Besançon University Hospital, France and is board certified in both radiology and cardiology.
Patient preparation: magnetic resonance imaging techniques -- Cardiovascular anatomy and atlas of MR normal anatomy -- MRI sequential segmental analysis and identification of anomalies -- Anomalous systemic and pulmonary venous connections -- Aortic arch anomalies, tracheal compression and stenosis -- Other aortic malformations -- Anomalies of the right ventricular outflow tract and pulmonary arteries -- Postoperative evaluation.
Electronic reproduction.
Keywords: Cardiovascular system -- Abnormalities -- Magnetic resonance imaging; Electronic books